Outcome of Ventral Fusion of Two or Three Cervical Vertebrae with a Locking Compression Plate for the Treatment of Cervical Stenotic Myelopathy in Eight Horses - Kühnle, Christoph; Fürst, Anton E.; Ranninger, Elisabeth; Suárez Sánchez-Andrade, José; Kümmerle, Jan M. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives It was recently shown that biomechanical stability achieved with a locking compression plate (LCP) for ventral cervical fusion in horses is similar to the commonly used Kerf cut cylinder. The advantages of the LCP system render it an interesting implant for this indication. The goal of this report was to describe surgical technique, complications and outcome of horses that underwent ventral fusion of two or three cervical vertebrae with an LCP.Methods Medical records of eight horses were reviewed for patient data, history, preoperative grade of ataxia, diagnostic imaging, surgical technique and complications. Follow-up information was obtained including clinical re-examination and radiographs whenever possible.Results Two (n = 5) or 3 (n = 3) cervical vertebrae were fused in a mixed population with a median age of 9 months, median weight of 330 kg and median grade of ataxia of 3/5. A narrow 4.5/5.0 LCP (n = 6), a broad 4.5/5.0 LCP (n = 1) and a human femur 4.5/5.0 LCP (n = 1) were applied. Two horses were re-operated due to implant loosening. Six patients developed a seroma. Long-term complications included ventral screw migration in four, spinal cord injury in one and plate breakage in two horses at 720 to 1116 days after surgery. Outcome was excellent in three, good in four, poor in one patient.Clinical Significance The use of an LCP for ventral cervical vertebral fusion is associated with good clinical results. However, a careful surgical technique is required to further reduce the complication rate.
Keywords: Wobbler syndrome; equine surgery; cervical fusion; locking plates; spine surgery